Penyuluhan Perilaku Hidup Bersih dan Sehat (PHBS) Bagi Pengelola dan Pedagang Pada Taman Wisata Loang Baloq Kota Mataram - Kurniawan, Edy; Dani, Husnul Budiatman; Zaki, Muhammad; Fahkrurrozi, Fahkrurrozi; Haryanti, Ramdhani; Multazam, Syamsul; Islami, Gita Nabilla; Aini, Aini; Muflihun, Sadiqin; Al-Ayuni, Yusfi; Ariani, Nining; Aji, Dunung Waskito; Taqiudin, Muhamad; Sari, Yuliani Budi Permata; Azmi, Lalu Sulthoni; Athiya, Faeruzza; Rahmawati, Khairul Pahmi; Prihartini, Dita; Kurniawati, Ari; Prajanati, Miftha Sukma Adi; Irawan, Ade; Adawiyah, Rabiatul (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
PHBS stands for Clean and Healthy Living Behavior outreach activity for managers and vendors at Loang Baloq Tourism Park in Mataram City aims to increase public awareness and knowledge in maintaining the cleanliness of the tourist environment. Through this activity, it is hoped that a clean, healthy, and comfortable tourist environment will be created for visitors and support the government's efforts to realize a sustainable tourism destination. The implementation method includes outreach, demonstrations, and direct assistance in the field. Community service partners are vendors and managers of Loang Baloq Tourism Park, totaling 20 participants. The evaluation was carried out in the form of a pre-test and post-test on the PHBS concept, the importance of a clean tourist environment, waste management, and hygiene practices in selling food and beverages. The results of the activity showed an 85% increase in participants' understanding of the importance of PHBS, based on the results of the pretest (average 57.75%) and posttest (85.25%), as well as a commitment to implementing clean and healthy behaviors in daily activities. The implementation of PHBS not only impacts individual health but also improves environmental quality and tourist attractions. Follow-up, including regular mentoring and policy support from local governments, is necessary to ensure sustainable PHBS implementation.